1984
DOI: 10.1073/pnas.81.10.3245
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of olefins by cytochrome P-450 model compounds: mechanism of oxygen atom transfer.

Abstract: The mechanism of the Mn(III) porphyrincatalyzed epoxidation of olefins by lithium hypochlorite is examined. The active oxidant is thought to be a high-valent manganese-oxo complex. It is shown that a relatively stable intermediate is reversibly formed upon interaction of the olefin and the oxo complex. The decomposition of this intermediate to Mn(III) porphyrin and epoxide is the rate-determining step of the catalytic cycle. Some analogies to the biochemical epoxidation of olefins catalyzed by cytochrome P-450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…CH 2 Cl 2 ) system, but the phase-transfer process and other side reactions complicated the interpretation of the kinetic data and led to controversial conclusions. [5] Montanari and co-workers demonstrated that by lowering the pH of the aqueous NaOCl solutions from 12.7 to 10.0 ± 0.5, HOCl can be extracted into the organic phase as a soluble terminal oxidant. [6] Under two-phase conditions in the absence of a phase-transfer catalyst, they also investigated the kinetic behavior of a (porphyrin)manganese-catalyzed olefin epoxidation system employing HOCl as the terminal oxidant and observed Michaelis-Menten saturation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…CH 2 Cl 2 ) system, but the phase-transfer process and other side reactions complicated the interpretation of the kinetic data and led to controversial conclusions. [5] Montanari and co-workers demonstrated that by lowering the pH of the aqueous NaOCl solutions from 12.7 to 10.0 ± 0.5, HOCl can be extracted into the organic phase as a soluble terminal oxidant. [6] Under two-phase conditions in the absence of a phase-transfer catalyst, they also investigated the kinetic behavior of a (porphyrin)manganese-catalyzed olefin epoxidation system employing HOCl as the terminal oxidant and observed Michaelis-Menten saturation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, there is little information about the fate of the added imidazoles during the oxidation reaction, although they were used in excess molar amounts as compared to the metalloporphyrin catalyst. 28) Our present results indicate that in certain cases, not only the substrate itself, but also the added imidazole might be oxidized, affording both the desired product and the oxidized imidazole.…”
Section: Resultsmentioning
confidence: 99%
“…These observations were offered in support of the accumulation of a metallaoxetane intermediate (6)(7)(8)(9)(10). If the reactions were zero-order in epoxide formation, then the accumulation of a compound of alkene and manganese-oxo species would be required.…”
mentioning
confidence: 99%
“…It has been reported (8,9,14) that at 200 to 890 turnovers of catalyst, when using initial rates: (i) epoxide formation was zero-order; (it) rates were dependent upon alkene concentration; (iii) rates were different for different alkenes; and (iv) one alkene inhibited the epoxidation of another. These observations were offered in support of the accumulation of a metallaoxetane intermediate (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation